2D transmission imaging with a crossed-array configuration for defect detection - Koch, Andreas; Gruber, Stefan; Scharrer, Thomas; Fendt, Karl; Lerch, Reinhard; Ermert, Helmut (2012 IEEE International Ultrasonics Symposium Proceedings, 2012)
Two-dimensional time of fight and attenuation measurements offer unique opportunities in nondestructive ultrasound testing for defect detection. However, unavailability or costs for 2D matrix transducers usually require a mechanical scanning procedure with a single element transducer to acquire 2D projections. This time and cost intensive process is not applicable for high speed testing of e.g. low cost devices. We propose a concept of a crossed-array configuration for 2D transmission imaging in terms of time of fight and attenuation measurements. A mechanical setup and a data acquisition system have been developed to evaluate the potential of this concept. Our results show, that ultrasound crossed-array transmission imaging has a great potential in terms of time of fight and attenuation measurements for defect detection in non-destructive testing, e.g. for detection of delaminations. With an appropriate data acquisition system transmission images can be acquired with frames rates in the kHz range. Therefore, crossed-array transmission imaging is a unique, cost efficient procedure with a good resolution for high speed testing in industrial applications. © 2012 IEE
Keywords: 2D projection; attenuation; crossed-array; speed of sound; time of fight; transmission imaging; ultrasound transmission

Investigation of the Synthetic Aperture Focusing Technique resolution for heavy rotor forging ultrasonic inspection - Fendt, Karl; Mooshofer, Hubert; Rupitsch, Stefan; Lerch, Reinhard; Ermert, Helmut (Ultrasonics Symposium (IUS), 2013 IEEE International, 2013)
This contribution determines the resolution achievable by Synthetic Aperture Focusing Technique (SAFT) processing ultrasonic inspection data acquired along circular scan paths. If the inspection is conducted using a transducer with a narrow divergence angle, the lateral resolution after SAFT reconstruction becomes highly depth dependent. In Nondestructive Testing (NDT), such a configuration is typical for the ultrasonic testing of heavy rotor steel forging blanks for energy industry components, such as rotor shafts and turbine discs. There, the inspection is performed in contact mode over specimen's mantle surface with longitudinal waves. For defect classification and quantification, knowledge of the resolution is essential. The radial dependency of the resolution is determined by SAFT processing simulated far field point spread functions at different depths. The simulation results are discussed and compared with actual inspection data of turbine disc forgings containing reference reflectors and natural indications.

Simulation assisted ultrasonic defect characterization in heavy rotor forgings - Fendt, Karl; Mooshofer, Hubert; Rupitsch, Stefan; Ermert, Helmut (AMA Conferences 2015 - SENSOR 2015 and IRS2 2015, 2015)

Ultrasonic Defect Characterization in Heavy Rotor Forgings by Means of the Synthetic Aperture Focusing Technique and Optimization Methods - Fendt, Karl; Mooshofer, Hubert; Rupitsch, Stefan; Ermert, Helmut (IEEE Transactions on Ultrasonics Ferroelectrics and Frequency Control, 2016)

Ultrasonic defect detection in multi-material, axis-symmetric devices with an improved synthetic aperture focusing technique (SAFT) - Scharrer, Thomas; Koch, Andreas; Fendt, Karl; Rupitsch, Stefan; Sutor, Alexander; Ermert, Helmut; Lerch, Reinhard (2012 IEEE International Ultrasonics Symposium Proceedings, 2012)
This paper describes an improved synthetic-aperture-focusing-technique (SAFT) for ultrasonic defect detection in multi-material devices with a circular cylindrical geometry. In conventional SAFT, defect imaging resolution in such specimen is limited, due to refraction at material interfaces. Hence, the improved technique allows to increase the probability of detection (POD) and the resolution of defects in multi-material, axis-symmetric devices. Especially, if defects are located in layers far away from the device surface and the discrepancies in the speed of sound (SOS) of the specimen materials are thoroughly substantial, it is indispensable to implicate refraction effects in the SAFT processing. Thereby, the examination is divided into three major steps. First, a specimen is scanned by rotating a spherically focused immersion ultrasound transducer around it. In a second step, a corrected time of flight (TOF) distribution is calculated by a fast marching method (FMM) with the à-priori knowledge of the specimen layout and the different SOS in the materials. As third and last step, the improved SAFT is performed utilizing the TOF distribution. To verify improvements in comparison to a conventional SAFT, a specimen is inspected, consisting of a steel and a polyvinyl chloride (PVC) part. © 2012 IEEE.